Liminality in paradise : a study in utopianism at the Punta Mona community - Jokivirta, Lisa (2009)
This Master’s thesis is a study in utopianism at the Punta Mona Sustainable Living and Education Centre, an ecological community of North Americans living on the Caribbean coast of Costa Rica. The mission statement of Punta Mona is to show “sustainability” as a lived reality and to inspire individuals to return to mainstream society to enact change towards a more “eco-conscious” world. The main objective of this thesis is to critically examine the concept of sustainability as it is understood and practiced at Punta Mona and to raise questions over the tensions inherent in Punta Mona’s in-between position as an ecological community and ecotourism venture. What power structures are implicitly embedded within Punta Mona’s talk of “sustainability”, “community” and “oneness”? Does Punta Mona ultimately challenge or reinforce Western conceptualizations, values and paradigms, and at what potential cost to local or subaltern forms of knowledge? Victor Turner’s concept of liminality will be used as the theoretical framework through which such questions will be explored. Punta Mona displays many characteristics of liminality as a “state of outsiderhood” or being on the margins of society. It creates a liminal space far removed from mainstream society in which important personal aspects such as identity, beliefs and ways of living can be put into play without affecting one’s place in the “real world”. However, this thesis argues that paradoxically, Punta Mona struggles with liminality due to its own liminal position between corporation and community, non-sustainability and sustainability, North and South, core and margin, and North America and Costa Rican society. The empirical material of this thesis is drawn from firsthand participatory and ethnographic fieldwork, and consists of 45 in-depth interviews with members of the Punta Mona Community, conducted in English and Spanish. Victor Turner’s concept of liminality is used to explore some of the paradoxes, ambiguities, boundaries and power tensions inherent in the fluidity of a living utopian experiment and to raise questions over its implications on contemporary political thought and life.